Graduación Centro universitario de Turrialba en el Paraninfo. (UNED, 2015)
En la mesa principal Victor Hugo Fallas Araya,Luis Guillermo Carpio Malavasi , Julia Li Vargas ,Beatrice Páez Vargas y Jenny Seas Tencio